Concrete 3D printing technology for sustainable construction: A review on raw material, concrete type and performance - Xiaonan Wang; Wengui Li; Yipu Guo; Alireza Kashani; Kejin Wang; Liberato Ferrara; Isabel Agudelo (Developments in the Built Environment, 2024)
This paper reviews recent developments and proposes perspectives for future research on three-dimensional printing concrete (3DPC). This review originally analyses the 3DP applications combined with concrete types that are classified into three groups: functional concrete, sustainable concrete, and special concrete. The 3DP technique shows different effects on concrete types due to various modification methods (e.g., nano-additive, fibre addition, and chemical reagent) and challenging requirements (e.g., anisotropy exploit and defect). Summarily, the oriented fibre of 3DPC is a double-edged sword, asking for optimal structural design for engineered cementitious composite (ECC), ultra-high-performance concrete (UHPC), and most fibre-improved concrete. The 3DP technique is not propitious to all concrete types, such as foam concrete, because the additional pressure in the printing process poses a huge disadvantage to foam stability. This paper also proposes the 3DPC protentional from the view of concrete features, which represents a contribution to advanced concrete technology and 3DPC development direction.